Avaliação funcional da junção esofagogástrica em obesos e sua relação com a doença do refluxo gastroesofágico - Ferreira, Juliete Vaz (2018)
Obesity has been identified as an important risk factor in the development of gastroesophageal reflux disease (GERD). However, the mechanism of this relationship is still not well described. Thus, the objective of this study was to evaluate the motor function of the esophagogastric junction (EGJ) in obese and its relationship with GERD. This is a cross-sectional descriptive study carried out between October 2016 and October 2017, with volunteers from the Hospital Universitário Walter Cantídio (HUWC). The research was approved by the Research Ethics Committee of the Universidade Federal do Ceará and all volunteers expressed written consent to participate in the study. Volunteers performed a clinical evaluation, with questionnaires and anthropometric measures, manovacuometry test was used to evaluate the maximal inspiratory pressure (MIP) and the high-resolution manometry (HRM) and ambulatory 24-h impedance-pH measurements. The study evaluated 21 volunteers with BMI ≥ 40 kg / m² and 26 volunteers from the control group with normal gastroesophageal reflux (GER) of the Laboratorio de Pesquisa em Gastroenterologia (LabGastro). Four groups were formed: normal BMI (n = 12), excess weight (n = 14), obese with acid exposure to the normal esophagus (n = 10) and obese with abnormal esophageal acid exposure (n = 11). There was difference between the groups studied for variables: gender, age and BMI. There was no significant difference between the symptoms of volunteers with BMI ≥ 40. In the MAR analysis the intragastric pressure (PIG) was higher in the group with BMI ≥ 40 with abnormal acid exposure (p = 0.001), the transdiaphragmatic pressure was also higher in this group (p = 0.014) compared to the normal BMI group. JEG inspiratory pressure was higher in the two groups with BMI ≥ 40 (p = 0.002) compared to the normal and overweight BMI groups. The contractile index of JEG (IC-JEG) was higher in the BMI group ≥ 40 with abnormal acid exposure in TH12 and TH24 respiratory maneuvers compared to the group with normal BMI. Despite the limitations with regard to the sample size and the differences between the evaluated groups, we can observe with the study that obesity causes motor alterations in JEG, especially in individuals with abnormal acid exposure.